CO-WORKERS SUPPORT AND JOB PERFORMANCE - PELIN, Irina Ioana; OSOIAN, Codruta (Studia Universitatis Babeș-Bolyai Oeconomica, 2021)
In the context of a global pandemic affecting businesses worldwide, management focus is oriented to what would enhance the employees’ work performance even in crisis situations. This paper aims to identify, explore and explain the relationships between social support, task performance and organizational citizenship behaviour as well as different demographic data which might influence these variables. The final goal is to propose relevant solutions and recommendations for managers and practitioners in human resources which could be easily applied and have a major impact on individual performance as well as on the overall performance of the organization. The quantitative research is based on a sociological survey consisting of two standardized questionnaires based on tested Likert scales measuring co-workers perceived support, employees’ task performance and organizational citizenship behaviour. The sample consists of 300 pairs of employees and their direct supervisors working in services companies based in Romania. The survey’s results are analysed by performing correlation and regression analyses in JASP 0.14.1.0 free software. The results show positive relationships between the variables yet it proves that co-workers’ support is not relevant for task performance. Valuable information regarding OCB and task performance can be added to the previous job performance research. Statistically significant relationships with demographic data could not be obtained. Further studies might consider a larger sample consisting of Europeans in more than one country as well as comparative analyses between countries and companies’ fields of activity. JEL classification: M12